ISOLATION, CHARACTERIZATION AND OPTIMIZATION OF PROCESS VARIABLES FOR PARTIALLY PURIFIED IMMOBILIZED Α-AMYLASE ISOLATED FROM INDIAN CHICKEN FEATHER - SHOBHA G; SHASHIDHARA K.S; ANANDA S (International Journal of Pharma and Bio Sciences, 2015)
Immobilization of α-Amylase produced by a Pseudomonas sp isolated from Indian Chicken feather was studied. Partially purified enzyme with 486.77 IU and specific activity of 811.28 units mg (protein)-1 was used for immobilization study. An easily available and inexpensive 3% Sodium alginate matrix with easy immobilization gel entrapment procedure was used for trapping the enzyme showed 555.5 IU activity. The optimization was carried out to study the catalytic properties which showed the optimum pH, temperature and substrate concentration at pH 7, 450C and 16mg, respectively. The reusability of the immobilized enzyme preparation showed its use in continuous starch hydrolysis for up to 10 cycles. This immobilized enzyme can be used as a replacement of commercial enzyme since it has shown same greater operational flexibility and enzymatic activity of the pure enzyme.